2015
DOI: 10.3390/foods4040581
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Growth Inhibition and Metabolism of Hydroxycinnamic Acids by Brewing and Spoilage Strains of Brettanomyces Yeast

Abstract: Brettanomyces yeasts are well-known as spoilage organisms in both the wine and beer industries, but also contribute important desirable characters to certain beer styles. These properties are mediated in large part by Brettanomyces’ metabolism of hydroxycinnamic acids (HCAs) present in beverage raw materials. Here we compare growth inhibition by, and metabolism of, HCAs among commercial brewing strains and spoilage strains of B. bruxellensis and B. anomalus. These properties vary widely among the different str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…This observation is in general agreement with published data for other strains that show weak or no inhibition of growth by this compound compared to other cinnamic acids (Harris et al, 2009). When a strain showed variation for inhibition by ferulic acid and p-coumaric acid, it's turned out that ferulic acid was always a more potent inhibitor (Lentz et al, 2015). This data supports results from similar experiments using different strains of B. bruxellensis and B. anomalus (Harris et al, 2009).…”
Section: Precursorssupporting
confidence: 82%
See 1 more Smart Citation
“…This observation is in general agreement with published data for other strains that show weak or no inhibition of growth by this compound compared to other cinnamic acids (Harris et al, 2009). When a strain showed variation for inhibition by ferulic acid and p-coumaric acid, it's turned out that ferulic acid was always a more potent inhibitor (Lentz et al, 2015). This data supports results from similar experiments using different strains of B. bruxellensis and B. anomalus (Harris et al, 2009).…”
Section: Precursorssupporting
confidence: 82%
“…Recently, Lentz et al (2015) showed that caffeic acid was the weakest inhibitor of the HCAs tested. This observation is in general agreement with published data for other strains that show weak or no inhibition of growth by this compound compared to other cinnamic acids (Harris et al, 2009).…”
Section: Precursorsmentioning
confidence: 99%
“…B. bruxellensis is the main spoilage yeast in winemaking, detrimental for wine quality and mainly responsible for volatile phenols release, but also of biogenic amine bioproducts and responsible for considerable economic losses [20,47,48]. In addition to reducing the risks of undesired microbial developments, biocontrol offers opportunities to reduce chemical preservatives such as SO 2 , associated with allergic manifestations in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial interest in these yeasts has resulted in a growing body of data related to their contribution to wine and beer flavor. Genetic and physiological analysis of B. bruxellensis strains that vary in geographical and source environment suggests niche adaptation, as strains cluster more strongly by the isolation environment than by geography [64][65][66][67][68]. There are notable differences between beer and wine strains at the whole genome level and for SNPs, including genes involved in volatile phenol production [66,67].…”
Section: Microbial Enzymatic Decarboxylation To Vinyl Derivativesmentioning
confidence: 99%